Internet usage to supplement in-class learning and students' attitudes on online content subscription / Normizah Mohd Som - Mohd Som, Normizah (2003)
This study looks at how the Internet could be used by secondary school students for learning purposes. The Internet offers a vast amount of information relevant to student's studies but often student's use of the Internet is limited to surfing the World Wide Web, emailing, chatting, playing online games and downloading files. A survey will be conducted on these students to look at how they use the Internet to help them in their studies, such as finding extra information related to their lessons and helping them do the homework. It will also look at several local educational websites to identify the key criteria and the contributing factors for qualifying as good educational websites. Finally, the study intends to find out whether students are willing to pay a subscription fee to access contents from the educational websites.